2005
DOI: 10.1111/j.1365-313x.2005.02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced salt tolerance mediated by AtHKT1 transporter‐induced Na+ unloading from xylem vessels to xylem parenchyma cells

Abstract: SummaryAtHKT1 is a sodium (Na þ ) transporter that functions in mediating tolerance to salt stress. To investigate the membrane targeting of AtHKT1 and its expression at the translational level, antibodies were generated against peptides corresponding to the first pore of AtHKT1. Immunoelectron microscopy studies using anti-AtHKT1 antibodies demonstrate that AtHKT1 is targeted to the plasma membrane in xylem parenchyma cells in leaves. AtHKT1 expression in xylem parenchyma cells was also confirmed by AtHKT1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
543
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(573 citation statements)
references
References 42 publications
27
543
0
3
Order By: Relevance
“…The function of xylem-localized HKT1 in limiting Na + translocation to the shoot has been established (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006;Davenport et al, 2007). In hkt1 mutants, xylem Na + concentration is higher than in the wild type (Sunarpi et al, 2005). In the nakr1-1 mutant, xylem sap Na + concentration was the same as in wildtype plants ( Figure 9A).…”
Section: Phloem and Na + /K + Homeostasismentioning
confidence: 65%
See 2 more Smart Citations
“…The function of xylem-localized HKT1 in limiting Na + translocation to the shoot has been established (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006;Davenport et al, 2007). In hkt1 mutants, xylem Na + concentration is higher than in the wild type (Sunarpi et al, 2005). In the nakr1-1 mutant, xylem sap Na + concentration was the same as in wildtype plants ( Figure 9A).…”
Section: Phloem and Na + /K + Homeostasismentioning
confidence: 65%
“…In theory, the amount of K + and Na + in leaves is determined by several distinct processes: Na + /K + uptake from the soil, longdistance transport to the shoot via the xylem, and redistribution through the phloem. The function of xylem-localized HKT1 in limiting Na + translocation to the shoot has been established (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006;Davenport et al, 2007). In hkt1 mutants, xylem Na + concentration is higher than in the wild type (Sunarpi et al, 2005).…”
Section: Phloem and Na + /K + Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…We found that AtHKT1 protects leaves from sodium accumulation by removing sodium from the xylem sap [3,4]. Several labs have now shown that orthologous HKT genes in the crops rice and wheat use the same mechanism as a major salinity tolerance mechanism and that long sought salinity resistance genetic loci (called QTL) map to these HKT transporter genes.…”
Section: What Is the Main Focus Of Your Studies?mentioning
confidence: 87%
“…Various reports have indicated that increasing cytosolic K + levels relative to Na + , thus, increasing the K + /Na + ratio, is crucial for Na + tolerance in plants and maintaining high K + /Na + ratio in shoots is highly correlated with salinity tolerance in glycophytes (Dubcovsky et al, 1996;Ren et al, 2005;Sunarpi et al, 2005;Mason et al, 2010). The Arabidopsis AtHKT1 protein, a Na + -K + cotransporter, mediates Na + influx when expressed in heterologous systems such as Xenopus oocytes, yeast and wheat (Mason et al, 2010;Laurie et al, 2002;Baek et al, 2011;Plett et al, 2010).…”
Section: Discussionmentioning
confidence: 99%